2018
DOI: 10.3389/fgene.2018.00245
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mutations in the Asparagine Synthetase Gene (ASNS) Associated With Microcephaly

Abstract: Microcephaly is a devastating condition defined by a small head and small brain compared to the age- and sex-matched population. Mutations in a number of different genes causative for microcephaly have been identified, e.g., MCPH1, WDR62, and ASPM. Recently, mutations in the gene encoding the enzyme asparagine synthetase (ASNS) were associated to microcephaly and so far 24 different mutations in ASNS causing microcephaly have been described. In a family with two affected girls, we identified novel compound het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 44 publications
1
24
1
Order By: Relevance
“…All the described patients including this report share common clinical features 1-17 but with variable severity of the disease. Microcephaly was evident by the second trimester of pregnancy in our patient and those described by Seidahmed et al 6 and Schleinitz et al 13 At birth, the majority (80%) of ASD patients showed congenital microcephaly. Nevertheless, progressive microcephaly was reported in all patients.…”
Section: Clinical Coursesupporting
confidence: 83%
“…All the described patients including this report share common clinical features 1-17 but with variable severity of the disease. Microcephaly was evident by the second trimester of pregnancy in our patient and those described by Seidahmed et al 6 and Schleinitz et al 13 At birth, the majority (80%) of ASD patients showed congenital microcephaly. Nevertheless, progressive microcephaly was reported in all patients.…”
Section: Clinical Coursesupporting
confidence: 83%
“…This mutation is located in a highly conserved region of the C-terminal domain of the protein, which contains the ASNS domain (Fig. 2a, c, d) 2,14 . The variant was not found in the Genome Aggregation Database (http://gnomad.broadinstitute.org/), the Exome Aggregation Consortium (http://exac.broadinstitute.org/), or ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/).…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal domain contains the glutamine-binding pocket for the amidotransferase reaction, while the C-terminal domain is the ASNS domain and contains the ATP-binding site (Fig. 2c, d) 2,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases of ASNSD reported from a variety of ethnic origins in the past few years (Abhyankar et al, 2018; Alfadhel et al, 2015; Ben‐Salem et al, 2015; Chen, Li, Wang, Chen, & Hong, 2019; Galada et al, 2018; Gataullina et al, 2016; Gupta et al, 2017; Palmer et al, 2015; Radha Rama Devi & Naushad, 2019; Ruzzo et al, 2013; Sacharow et al, 2018; Schleinitz et al, 2018; Seidahmed et al, 2016; Sprute et al, 2019; Sun et al, 2017; Yamamoto et al, 2017), have been summarized in Table 1 with information on nucleotide changes, amino acid changes, and the corresponding genotypes. ASNSD is considered ultrarare in China, with only one case reported in July 2019 (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%